2013
DOI: 10.7205/milmed-d-12-00286
|View full text |Cite
|
Sign up to set email alerts
|

MEDEVAC: Survival and Physiological Parameters Improved With Higher Level of Flight Medic Training

Abstract: There is a statistically significant improvement in the HCT, BD, SpO 2 , and 48-hour survivability at the CSH in the cohort transported by the CCFP group when compared to the cohort transported by the EMT-B group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The US military employs both DUSTOFF evacuation helicopters staffed with a medic capable of providing basic life support and the PEDRO air evacuation teams, which include on-board fighting paramedics. Continued efforts are made to upgrade the level of training of these teams, promoting improved medical and operational capabilities (34). The British Royal Air Force operates the MERT, a platform manned by two paramedics, one physician and a nurse, capable of providing advanced life-saving interventions, including transfusion of blood products.…”
Section: Medical Evacuationmentioning
confidence: 99%
“…The US military employs both DUSTOFF evacuation helicopters staffed with a medic capable of providing basic life support and the PEDRO air evacuation teams, which include on-board fighting paramedics. Continued efforts are made to upgrade the level of training of these teams, promoting improved medical and operational capabilities (34). The British Royal Air Force operates the MERT, a platform manned by two paramedics, one physician and a nurse, capable of providing advanced life-saving interventions, including transfusion of blood products.…”
Section: Medical Evacuationmentioning
confidence: 99%
“…Given that our study found that short evacuation times appear to confer the greatest benefit in those patients suffering from NCTI + AMP and other studies have found NCTI to be a leading cause of preventable combat mortality [ 7 , 9 ], when feasible, evacuation times of patients with NCTI should remain under 30 min. In those circumstances where transport of NCTI patients from the POI to a Role 2/3 facility is not possible, rapid access to blood products, forward deployed advanced medical providers and advanced en route care capabilities, and/or resources for the control of NCTI may decrease mortality [ 1 , 2 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aeromedical evacuation platforms such as MEDEVAC allow for urgent evacuation to medical treatment facilities (MTF) that can provide the more complex, necessary lifesaving interventions that are not otherwise possible at point of injury (POI) or en route. Transport times may vary depending on environmental factors and the ability to land in combatant locations [ 2 ]. Urgent response and transport can be delayed due to tactical issues, which may interfere with timely life-saving care.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have been conducted evaluating the en route care of patients during transport from point of injury to first MTF (role 2 and/or 3) 5,12,[14][15][16][17][18][19][20][21][22] and out of theater to the role 4 medical center in Landstuhl, Germany. 12,[19][20][21][22][23][24][25][26][27][28] A few published reports have described patients treated by individual forward surgical teams (role 2) during specific deployments, but these studies do not include information related to patient transport.…”
Section: Discussionmentioning
confidence: 99%